2017
DOI: 10.1002/2327-6924.12531
|View full text |Cite
|
Sign up to set email alerts
|

Current state of screening high-ACE youth and emerging adults in primary care

Abstract: Background and purpose Trauma comes in many forms, including interpersonal, community, and institutional trauma. The adverse childhood event (ACE) studies demonstrated that adverse experiences in childhood can have a profound, cumulative impact on the course of health and development over a lifetime. It is critical for healthcare providers, such as nurse practitioners (NPs), working in primary care to screen adolescents and emerging adults for a history of ACEs and trauma. A review of current assessment tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Finkelhor (2017) has suggested that screening for these adverse childhood experiences may be premature, arguing that clinically efficient tools for such screening are currently lacking. Other scholars have noted a lack of specificity with regard to identifying individuals at greatest risk for future health problems and a lack of consensus as to which types of adversity are the most important predictors of higher CRP and cardiovascular risk (Pardee et al ., 2017). While our results and those of others (Danese et al ., 2007, 2008) confirm a relationship between childhood maltreatment and risk for chronic inflammation, these new findings suggest that caution is needed before screening for adverse childhood experiences with self-report inventories is implemented on a large-scale basis.…”
Section: Discussionmentioning
confidence: 99%
“…Finkelhor (2017) has suggested that screening for these adverse childhood experiences may be premature, arguing that clinically efficient tools for such screening are currently lacking. Other scholars have noted a lack of specificity with regard to identifying individuals at greatest risk for future health problems and a lack of consensus as to which types of adversity are the most important predictors of higher CRP and cardiovascular risk (Pardee et al ., 2017). While our results and those of others (Danese et al ., 2007, 2008) confirm a relationship between childhood maltreatment and risk for chronic inflammation, these new findings suggest that caution is needed before screening for adverse childhood experiences with self-report inventories is implemented on a large-scale basis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite results indicating the key role that positive experiences in childhood can play in predicting later health and wellbeing in the context of adversity, this body of research has not been fully integrated into public health and policy. Alternatively, screening for adults' histories of ACEs or their children's current ACEs is more commonly recommended in some areas of primary care and pediatrics, particularly in communities where children might be at high risk for ACEs (Bright et al 2015;Glowa, Olson, and Johnson 2016;Pardee et al 2017). The inclusion of instruments to examine positive childhood experiences, in addition to the more common screening of adversity, is essential to better understanding the resilience resources linked to better long-term adaptation and the mechanisms through which both adverse and positive childhood experiences interplay to predict adulthood and intergenerational adaptation.…”
Section: Positive Childhood Experiences As a Counterpart To Childhood Adversitymentioning
confidence: 99%
“…There is an urgent need to develop interventions to mitigate the impact of ACEs on adolescent and women’s sexual and reproductive health, especially in delaying sexual initiation among Black women. The incorporation of ACE screening during routine care can help identify the most at-risk individuals to facilitate referrals, undergo targeted interventions, and help to delay sexual initiation and its associated consequences [45, 46]. Parent-based interventions and adolescent-only interventions have demonstrated success in delaying sexual initiation.…”
Section: Discussionmentioning
confidence: 99%